PENGARUH PENDEKATAN SAINTIFIK TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS SISWA KELAS VII SMP IT BUDI LUHUR CIMAHI PADA MATERI BENTUK ALJABAR - Dewi Ramadhona; Heris Hendriana; Rippi Maya; M. Afrilianto (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This research is a classroom action research with stages that include planning, implementing action, observing, and reflecting. This study aims to describe how to improve students' mathematical understanding skills when using a scientific approach to algebraic form material. This research was conducted on 21 students of grade VII SMP IT Budi Luhur academic year 2021/2022. The instrument used in this study was 5 questions referring to the indicators of understanding ability given at the beginning of learning and at the end of learning, which were then analyzed by calculating the average value of each question that would be done with Ms. Excel. Data processing was carried out using qualitative descriptive analysis. The results showed that the ability of mathematical understanding can be improved using a scientific approach.